Evidence-Based Practices of Nurses Regarding Nosocomial Infection in ICU. A Descriptive study: Practices of Nurses Regarding Nosocomial Infection in ICU - Riaz, Sumaira; Afzal, Muhammad; Ali, Afsar; Khan, Sadia (Pakistan Journal of Health Sciences, 2023)
Nosocomial infections influence patients’ lives over lengthy hospitalization, illness, and death, following important costs to both health organizations and society. Evidence-based practice is observed as a system to carry out health care that is additionally effective and important in the current health care setting. Objective: To identify the level of evidence-based practices of nurses regarding nosocomial infection in the intensive care units. Methods: A cross-sectional descriptive study design was used. The population was the ICU staff nurses of the Tertiary Care Hospital, Lahore. The duration of the study with 09 months after the synopsis approval. The sample size of 72 nurses has calculated a population size 95 confidence interval and a margin of error of 5%. A convenient sampling Technique was used in this study. The questionnaire was consisting of 4 items and 31 questions. Ethical Considerations were maintained. Data were kept confidential and secure by coding. Data were analyzed by SPSS version 21. Results: The highest percentage of staff nurses in this study were females (98.6%) and aged between 26-35 years (76.4%) and diploma holder were (69.4%). Nurses who have experience less than 10 years were 45.8%. Most of the participants were performing hand hygiene practicing frequently (59.7%) whereas (16.7%) were performing rarely before contact with patient. Highest percentage of participants (77.8%) were using personal protective equipment’s. Conclusions: Evidence-Based Knowledge related to nosocomial infection is adequate among nurses. Hand hygiene performance is adequate as compared to international standards.